The Panama canal: its history, its political aspects, and financial difficulties (1885)
This publication describes openly the truth about the Panama Canal, its history and its economic difficulties particularly in Central America. / Abstract. Esta publicación describe abiertamente la verdad sobre el Canal de Panamá, su historia y sus dificultades económicas en particular con Centro América.